2013
DOI: 10.1021/jp3096538
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Intramolecular Excited State Proton Transfer in Emission Tunable, Highly Luminescent Imidazole Derivatives

Abstract: The enol–keto excited state dynamics of a series of emission tunable imidazole derivatives undergoing excited state intramolecular proton transfer (ESIPT) were determined by means of steady state and time-resolved spectroscopic techniques in different solvents at room temperature and at 77 K. Examination of the corresponding non-ESIPT compounds, with the proton transfer function deliberately blocked, was carried out for comparison. At room temperature, the ESIPT process in the examined samples, determined by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…In the excited state the proton may be transferred from amine group (NH) to keto group (C=O) through ESIPT process leads to the existence of both KHB and EHB forms [18][19][20][21][22][23]33]. In dual emission, the low intensity peak at 410 nm arises from the normal ketamine form and the red shifted high intensity peak at 435 nm corresponds to the stable tautomeric enolimine form.…”
Section: Electronic Emission Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…In the excited state the proton may be transferred from amine group (NH) to keto group (C=O) through ESIPT process leads to the existence of both KHB and EHB forms [18][19][20][21][22][23]33]. In dual emission, the low intensity peak at 410 nm arises from the normal ketamine form and the red shifted high intensity peak at 435 nm corresponds to the stable tautomeric enolimine form.…”
Section: Electronic Emission Spectramentioning
confidence: 99%
“…This hypothesis leads to the concept of twisted intramolecular charge transfer (TICT) process. A number of reports have shown that the degree of steric hindrance plays an important role in dual emission arises from twisted intramolecular charge transfer (TICT) or excited state intramolecular proton transfer (ESIPT) process [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, for generalization, we lift the boundary of the unimolecular‐type ESIPT and extend the research to systems in which the proton donor (‐NHR) and acceptor are greatly separated, precluding the formation of an intramolecular H‐bond. Therefore, the occurrence of excited‐state proton transfer (ESPT), if available, requires the assistance of surrounding solvent molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The imidazole nucleus is a key building block that has been extensively used in anion sensors, ionic liquids, as well as electronic and optical materials . Triphenylimidazoles played an important role in the discovery of chemiluminescence, for this purpose tetraarylimidazoles have recently attracted significant interest . Nevertheless, the effects of substituent groups on the imidazole ring on the photochromic properties are not clear.…”
Section: Introductionmentioning
confidence: 99%